Controlling Product Risks when Consumers are Heterogeneously Overconfident: Producer Liability vs. Minimum Quality Standard Regulation - Andrzej Baniak; Peter Grajzl (Center for Economic Studies and ifo Institute (CESifo), 2014)
Contributing to the literature on the consequences of behavioral biases for market outcomes and institutional design, we contrast producer liability and minimum quality standard regulation as alternative means of social control of product-related torts when consumers are heterogeneously overconfident about the risk of harm. We elucidate the role of factors shaping the relative desirability of strict liability vis-à-vis minimum quality standard regulation from a social welfare standpoint. We also clarify when and why joint use of strict liability and minimum quality standard regulation welfare dominates the exclusive use of either mode of social control of torts.
Keywords: K13; L51; D81; D03; 330; product risk; overconfidence; consumer heterogeneity; tort law; minimum quality standard